Empowering Almaty's disabled workforce: action for inclusive labor market (Journal of Economic Research & Business Administration, 2024)
The inclusion of people with disabilities in all spheres of public life is an important political issue in the country. However, according to the Ministry of Labour and Social Protection of the Population of the Republic of Kazakhstan, only 25% of people with disabilities under the age of 55 are employed in Kazakhstan. Most of them are predominantly employed in low-paid industries, as well as in areas where physical labor is required. The state implements numerous programs, projects, and creates favorable conditions for people with disabilities, but employment remains consistently low. My research reveals a multifaceted issue: employers' reluctance to offer suitable conditions for individuals with disabilities, hindering their access to common infrastructure. In Almaty, my findings indicate that some individuals opt to reside with family members who can fulfill their basic needs. Additionally, there is a deficiency in adequate education and experience among this demographic. The author conducted structured and unstructured face-to-face interviews and telephone surveys with various people with disabilities, employers, and government agencies to understand the barriers to employment for people with disabilities in Almaty. Most of the previous research has focused on people with disabilities in other regions of Kazakhstan, while my research has focused on the problems of people with disabilities in Almaty. In conclusion, the author makes recommendations to the local administration and the Ministry of Labour and Social Protection of the Population of the Republic of Kazakhstan.Key words: Disability, social policy, labor market, social inclusion, inclusive education, barriers to employment.